Optimism, coping, and adaptation in older women. - Boland, Anne. (University of Ottawa (Canada), 1995)
This study looked at the relations among optimism, perception of stress, coping, and adaptation in women over the age of 60. It was hypothesized that optimism in older women would be associated with lower levels of perceived stress, a greater propensity to appraise stressors as challenges rather than as threats or losses, more adaptive coping strategies, fewer symptoms of distress, and higher levels of life satisfaction. The study used a prospective correlational design. One hundred and thirteen women took part in two interviews, separated by a minimum interval of three months. Although optimism was found to be correlated with most of the dependent variables (DVs), hierarchical regression analyses revealed that it lost its predictive power when the effects of the covariates, particularly Time 1 measures of the DVs and neuroticism, were statistically removed. The most important predictors of coping, distress, and life satisfaction were initial measures of these variables, followed by neuroticism. The discussion of the findings revolved around the importance of clarifying the construct of optimism. It was concluded that more research is needed to determine whether it is best conceptualized as bipolar or two-dimensional; in the latter case, optimism and pessimism would be related but separate constructs. Furthermore, the relationship of these constructs with neuroticism and extraversion needs to be further clarified. The results raise the question of whether the constructs of optimism and pessimism are subsumable under one or more of the "Big Five" personality factors (i.e., neuroticism, extraversion, openness, agreeableness, and conscientiousness).
Keywords: Women's Studies.